Comparative Analysis of Neuropeptides in Homologous Interneurons and Prohormone Annotation in Nudipleuran Sea Slugs - Lee, Colin A.; Romanova, Elena V.; Southey, Bruce R.; Gillette, Rhanor; Sweedler, Jonathan V. (Frontiers in Physiology, 2021)
Despite substantial research on neuronal circuits in nudipleuran gastropods, few peptides have been implicated in nudipleuran behavior. In this study, we expanded the understanding of peptides in this clade, using three species with well-studied nervous systems, Hermissenda crassicornis, Melibe leonina, and Pleurobranchaea californica. For each species we performed sequence homology analysis of de novo transcriptome predictions to identify homologs to 34 of 36 prohormones previously characterized in the gastropods Aplysia californica and Lymnaea stagnalis. We then used single cell mass spectrometry to characterize peptide profiles in homologous feeding interneurons: the multifunctional ventral white cell (VWC) in P. californica and the small cardioactive peptide B large buccal (SLB) cells in H. crassicornis and M. leonina. The neurons produced overlapping, but not identical, peptide profiles. The H. crassicornis SLB cells expressed peptides from homologs to the FMRFamide (FMRFa), small cardioactive peptide (SCP), LFRFamide (LFRFa), and feeding circuit activating peptides prohormones. The M. leonina SLB cells expressed peptides from homologs to the FMRFa, SCP, LFRFa, and MIP-related peptides prohormones. The VWC, previously shown to express peptides from the FMRFa and QNFLa (a homolog of A. californica pedal peptide 4) prohormones, was shown to also contain SCP peptides. Thus, each neuron expressed peptides from the FMRFa and SCP families, the H. crassicornis and M. leonina SLB cells expressed peptides from the LFRFa family, and each neuron contained peptides from a prohormone not found in the others. These data suggest each neuron performs complex co-transmission, which potentially facilitates a multifunctional role in feeding. Additionally, the unique feeding characteristics of each species may relate, in part, to differences in the peptide profiles of these neurons. These data add chemical insight to enhance our understanding of the neuronal basis of behavior in nudipleurans and other gastropods.